How an Anode‐Sided Gap Influences the Electrooxidation of Phenols in Flow Reactors - Jonas Wolf; Nijiati Yasheng; Dr. Julian Tobias Kleinhaus; Dr. Kevinjeorjios Pellumbi; Leon Wickert; Dr. Daniel Siegmund; Prof. Dr. Ulf‐Peter Apfel (ChemElectroChem)
Abstract Electroorganic synthesis offers a sustainable way to valorize chemical building blocks through renewable energy and environmentally friendly reagents. Substituted quinones, vital for manufacturing supplements, pharmaceuticals, and pesticides, are typically derived from phenols via thermochemical oxidation with inorganic oxidizers and specialized catalysts. Electrochemistry's ability to omit such components highlights the appeal of electrifying this process. This study explores the electrochemical oxidation of 2,3,5‐trimethylphenol (TMP) into trimethyl‐1,4‐benzoquinone (TMQ) – a crucial intermediate for vitamin E production – using a zero‐gap electrolyzer. A TMQ yield of 18 % and selectivity of 22 % were achieved, improving to 35 % and 37 %, respectively, with an anode‐sided spacer. We sought to identify factors promoting TMQ formation in reactors with an anode‐sided gap, addressing limitations in zero‐gap configurations and investigating the dependency on half‐cell potential, local reactant concentrations, pH, and electrolyte convection. The results revealed that the local substrate concentration is interrelated with electrolyte convection and is the most critical factor responsible for the gap‐related effect. A TMQ yield and selectivity of 33 % and 32 % were achieved in continuous flow conditions in a zero‐gap electrolyzer at optimized conditions. These findings underscore the critical role of local reactant concentrations in scaling synthetic electrochemical reactions, providing a robust framework for tackling future challenges in the field.